Urea and chronic kidney disease: the comeback of the century? (in uraemia research). Issue 1 (12th April 2017) - Vanholder, Raymond; Gryp, Tessa; Glorieux, Griet
Abstract: Urea, a marker of uraemic retention in chronic kidney disease (CKD) and of adequacy of intradialytic solute removal, has traditionally been considered to be biologically inert. However, a number of recent experimental data suggest that urea is toxic at concentrations representative for CKD. First of all, at least five studies indicate that urea itself induces molecular changes related to insulin resistance, free radical production, apoptosis and disruption of the protective intestinal barrier. Second, urea is at the origin of the generation of cyanate, ammonia and carbamylated compounds, which as such all have been linked to biological changes. Especially carbamylation has been held responsible for post-translational protein modifications that are involved in atherogenesis and other functional changes. In observational clinical studies, these carbamylated compounds were associated with cardiovascular and overall morbidity and mortality. These findings shed new light on the validity of Kt / V urea as a marker of dialysis adequacy. Yet, also the views that the kinetics of urea are not representative of the kinetics of several other uraemic retention solutes, and that urea cannot be held responsible for all complex metabolic and clinical changes responsible for the uraemic syndrome, still remain valid. Future efforts to improve the outcome of patients with CKD might be directed at further improving removal of solutes implied in the uraemic syndrome, including but not restricted to urea, also taking into account the impact of the intestine and (residual) renal function on solute concentration.